Validasi E-Book Proklamasi Kemerdekaan di Berbagai Daerah di Indonesia untuk Meningkatkan Kesadaran Sejarah Siswa - Novita, Dian; Aisiah, Aisiah (Jurnal Kronologi, 2025)
Local history learning in high schools has so far received less attention, one of which is the material on the news of the proclamation of Indonesian independence in various regions (localities) in Indonesia. This is due to the availability of learning resources that are not optimal in schools and researchers are developing special textbooks on the material of the proclamation of Indonesian independence in various regions. The purpose of this study is to validate the feasibility and practicality of the e-book developed to increase historical awareness of high school students. The research subjects involved 4 history lecturers as material validators and media validators, 1 history teacher and 33 students of SMA N 1 Rao as respondents for the practicality of the e-book of the proclamation of Indonesian independence. Data collection used a feasibility test instrument, and the practicality test of the e-book of the proclamation of Indonesian independence was in the form of a validation sheet in the form of a Likert scale. This study applies a quantitative approach using an average formula. The findings of this study indicate that; 1) the e-book material of the proclamation of independence in various regions in Indonesia according to the assessment of the material validator is categorized as feasible (the average score of the material validator is 3.25); 2) The e-book on the e-book on the proclamation of independence in various regions of Indonesia, according to the assessment of the teaching materials validator, is categorized as feasible (average score of 3.62); 3) the e-book on the proclamation of independence in various regions of Indonesia is categorized as very practical for implementation in history learning (average teacher score of 3.75 and average student assessment score of 3.53). Overall, it can be concluded that the e-book on the proclamation of Indonesian independence is categorized as very feasible and practical for implementation in history learning.